The The role of Hyperhomocysteinemia in the Pathogenesis of Ischemic Stroke: A Review of Current Clinical Research - Herchi, Nadia; Fahim, Knieszko; Franaszek, Jakub; Herchi, Sara; Jabrzyk, Martyna; Jarczyńska, Patrycja; Kijowski, Wojciech; Klusek, Mateusz; Michalak, Karolina; Przybył, Maciej (Journal of Education, Health and Sport, 2026)
Introduction. Hyperhomocysteinemia (HHcy) is often associated with the risk of stroke, which is one of the most common causes of death and disability in adults worldwide. The medical literature indicates a multidirectional effect of this amino acid on atherosclerotic and neurotoxic processes by inducing oxidative stress and promoting a prothrombotic state.The pathogenesis is further characterized by direct endothelial damage and epigenetic dysregulation. Together, these processes disrupt the structural and functional integrity of the cerebrovascular system, consequently leading to stroke. Aim of the study. The aim of this study is to evaluate the biochemical and clinical impact of HHcy on stroke development and to assess the validity of monitoring plasma Hcy levels in patients at risk for cerebrovascular disease. Materials and methods. The articles available in major medical databases such as Pubmed or Google Scholar are the basis of this research review. The study was conducted with the use of keywords like ‘HOMOCYSTEINE’, ‘HIPERHOMOCYSTEINEMIA’, ‘STROKE’, ‘ISCHEMIC STROKE’. Conclusions. Hcy is a key, modifiable risk factor for ischemic stroke that significantly worsens prognosis and leads to disability. According to the authors, the standards of neurological care should be revised to include routine monitoring of this amino acid and maintaining a level below 10 umol/L. Detecting stroke early and lowering Hcy levels in people at risk may become an important part of modern stroke prevention. However, further clinical studies are needed to confirm the long-term effect of these measures on case numbers.